Conservation of function and regulation within the Cdc28/cdc2 protein kinase family: characterization of the human Cdc2Hs protein kinase in Saccharomyces cerevisiae. - Wittenberg, C (1989)
Whereas the Cdc28 protein kinase of the budding yeast Saccharomyces cerevisiae plays an essential role in cell cycle progression during the G1 interval, a function in the progression from the G2 interval into M phase has been inferred for its homologs, including the Cdc2Hs protein kinase of humans. To better understand these apparently disparate roles, we constructed a yeast strain in which the resident CDC28 gene was replaced by its human homolog, CDC2Hs. This transgenic yeast strain was able to perform the G1 functions attributed to the Cdc28 protein kinase, including the ability to grow and divide normally, to respond to environmental signals that induce G1 arrest, and to regulate the Cdc2Hs protein kinase appropriately in response to these signals.